A systematic review and illustrative case presentation of Low-grade myofibroblastic sarcoma (LGMS) of the extremities - Schenker, Astrid; Gutjahr, Ewgenija; Lehner, Burkhard; Mechtersheimer, Gunhild; Wardelmann, Eva; Klotz, Rosa; Kalkum, Eva; Schiltenwolf, Marcus; Harhaus-Wähner, Leila; Renkawitz, Tobias; Panzram, Benjamin (Journal of Clinical Medicine, 2023)
Introduction: Low-grade myofibroblastic sarcoma (LGMS) is a rare tumor entity which occurs in the subcutaneous and deep soft tissues; it is less common in the bone with a predilection for the extremities and the head and neck region. As confirming the diagnosis is difficult and treatment strategies are not standardized, we aimed to identify patient and tumor characteristics, and to summarize treatment strategies and their clinical outcomes to guide surgeons. Methods: Included were full articles reporting patients with histology of LGMS in the extremities, excluding tumors of the trunk. All patients underwent surgery but with different extend, from marginal to wide resection. Included studies should inform about local recurrence, metastasis, or evidence of disease, depending on the surgical treatment. We conducted a structured search using MEDLINE (via PubMed), Web of Science, EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) to identify studies on low-grade myofibroblastic sarcoma of the extremities. Study designs like randomized controlled trials, systematic reviews, prospective trials, retrospective studies, and case reports were included. Prospective studies and comparative studies were not available at all. Therefore, meta-analysis was not possible and statistical analysis was purely descriptive. Results: Of the 789 studies identified from our initial search, 17 studies including 59 cases reported LGMS of the extremities with the surgical treatment and clinical outcome and were therefore analyzed. In addition, we present the rare case and surgical management of a 28-year-old male patient with residual LGMS of the thumb after an initial incomplete resection. The current literature suggests that a wide excision with R0 margins should be considered the standard treatment for LGMS. In cases where surgery leads to significant functional impairment, individual options like free tissue transfer from a donor site have to be considered. Therefore, we also present an illustrative case. For all selected case series and case reports, a high risk of confounding, selection bias, information bias, and reporting bias must be anticipated. Nevertheless, this systematic review provides a comprehensive overview on surgical treatment and clinical outcomes in LGMS surgery of the extremities.